The origin of the history of science in classical antiquity - Zhmudʹ, L. I͡A. (Leonid I͡Akovlevich) (Peripatoi, 2006)
Presents a comprehensive study of what remains of the writings of Aristotle's student Eudemus of Rhodes on the history of the exact sciences. This work presents an analysis of the trends in Presocratic, Sophistic and Platonic thought that contributed to the development of the history of science.